Formation and performance of highly absorbing solar thermal coating based on carbon nanotubes and boehmite. (15th July 2016) - Bera, Raj Kumar; Mhaisalkar, Subodh Gautam; Mandler, Daniel; Magdassi, Shlomo
Graphical abstract: A highly absorbing solar thermal coating composed of an absorbing CNT layer and an antireflective AlOOH layer is fabricated by a simple and low cost spray deposition. The resulting coating shows high absorptance of 97.5% in the entire solar spectrum along with excellent adhesion of 95–100% and high thermal stability of 450 °C for 50 h. Highlights: New highly solar absorbing coating for solar thermal applications. Coating is composed of carbon nanotubes and a top coat of boehmite. Coated is applied by simple spraying. Very high absorptance (ca. 97.5%), increased thermal stability and excellent adhesion to Al substrate. Abstract: A major component of solar thermal systems is the solar absorber, which converts light into heat. We report on achieving high absorptance, excellent adhesion, and high thermal stability of carbon nanotube-based black coatings by applying a layer of Boehmite (AlOOH) on top of the carbon nanotube (CNT) film by solution-processed spray deposition. The CNT layer made-up by spraying, functions as an absorbing layer and the AlOOH serves as an anti-reflecting and protecting film. The anti-reflecting property of AlOOH layer effectively increases the absorptance of CNT coating by decreasing the reflectance. The effect of the thickness of AlOOH layer on the absorptance, adhesion, and thermal stability of the resulting CNT/AlOOH coating was investigated. The CNT/AlOOH coating with optimized thickness of AlOOH layer shows very high absorptance ( α ) of 0.975. The adhesion of the coating is in the range of 95–100% with significant increase of thermal stability. This new approach is expected to open new possibilities for fabricating low-cost, highly efficient and thermally stable solar-thermal devices which are based on simple coating processes.